Projecting Citizenship : Photography and Belonging in the British Empire - Moser, Gabrielle (Book collections on Project MUSE., 2019)
"Examines the relationship between photography and citizenship, through a comprehensive account of the Colonial Office Visual Instruction Committee's lantern slide lecture scheme: a project initiated by the British government at the beginning of the twentieth century that aimed to photograph the entirety of the empire"--Provided by publisher